Analysis of the Special Method of Tafsir Al-Maraghi in Surah Ath-Thariq - Syifa Nur Saufa; Nida Ul Husna; Siti Shofiyah; Eni Zulaiha; Wildan Taufiq (al-Afkar, Journal For Islamic Studies, 2025)
Sheikh Ahmad Mustafa Al-Maraghi is a famous Muslim cleric and scholar from Egypt. He is known as the author of Tafsir Al-Maraghi, a monumental work which has become the main reference in the study of tafsir among Muslims. The general method used by Al-Maraghi in his interpretation is the tahlili method. The special method used by Al-Maraghi, namely stating the title in the form of the name of the letter, explaining the muqaddimah briefly, reviewing the syarhul mufrodat, explaining the meaning of ijmali, interpreting the verses, and mentioning the maqashid suroh (points of interpretation). In this research, the stages of Al-Maraghi's interpretation of QS.Ath-Thariq will be explained. The method used in this research is through literature study and analyzed using qualitative data analysis techniques. Al-Maraghi's Tafsir style contained in QS.Ath-Thariq is with an adabi ijtima'I and ilmi or empirical scientific approach.